A case of endometrial tuberculosis complicated by Pott’s spine with paraplegia - Wafai, N. A.; Seth, Shikha; Singh, P. S. (International Journal of Research in Medical Sciences, 2017)
Extra-pulmonary tuberculosis has shown an increasing trend in developing countries and accounts for 15-20% of total tuberculosis cases in India. Extra-pulmonary cases are usually diagnosed late due to vague and subtle signs & symptoms at a stage when major irreversible tissue damage had occurred. Tuberculosis is a chronic disease with infection remaining dormant for years in body to get activated whenever the immunity decreases. Spinal and cranial TB has the gravest manifestations, while the abdominal, female genital or pelvic TB poses a challenge because of lack of specific diagnostic tests. Here we are reporting a case of endometrial tuberculosis which was diagnosed very late, followed by treatment default and finally got complicated with Pott’s spine with paraplegia due to haematogenous spread. Timely intervention and anti-tubercular treatment improved the symptoms. It stresses on keeping the high suspicion of tuberculosis in unresponsive and persistent general symptoms.